Cyclic behavior of partially precast steel reinforced concrete short columns: Experiment and theoretical analysis. (15th November 2019) - Xue, Yicong; Yang, Yong; Yu, Yunlong
Highlights: Two novel precast steel reinforced concrete (SRC) composite columns are presented. Cyclic test and analysis on ten short column specimens were conducted. A novel analytical model is proposed to calculate the shear capacity of SRC columns. Abstract: Two innovative precast steel reinforced concrete columns are presented in this paper. The partially precast steel reinforced concrete (PPSRC) column was composed of a precast outer part and a cast-in-place inner part, and the hollow precast steel reinforced concrete (HPSRC) column kept the column core hollow to further reduce the column deadweight. In this paper, six PPSRC column specimens and four HPSRC column specimens with low aspect ratios were subjected to reversal cyclic load and constant axial compression to explore the cyclic behavior, which was evaluated by the failure mode, hysteresis characteristic, stiffness degradation, energy dissipation capacity and displacement ductility. Meanwhile, the effects of section shape, axial compression, ratios of longitudinal and transverse reinforcement and concrete strength of the inner part were critically investigated. The test results indicated that the column specimens suffered flexural-shear failure mode and shear-critical failure mode according to different ratios of longitudinal reinforcement, and, in general, the PPSRC columns exhibited more satisfactory cyclic behavior than that of the HPSRC columns. When the other parameters were the same, a higher stirrup ratio and lower axial compression led to a more satisfactory energy dissipation capacity, stiffness degradation and higher displacement ductility, and the load-bearing capacity increased with increasing inner concrete strength, stirrup ratio and axial compression. Based on the test results, an analytical model was established to calculate the shear capacity of test specimens, and the proposed model was verified to be valid using a test database consisting of 66 shear-critical SRC column specimens.